Simultaneous Dual-Color Fluorescence Microscope: A Characterization Study - Zheng Li; Xiaodong Chen; Liqiang Ren; Jie Song; Yuhua Li; Bin Zheng; Hong Liu (Analytical Cellular Pathology)
Background: High spatial resolution and geometric accuracy is crucial for chromosomal analysis of clinical cytogenetic applications. High resolution and rapid simultaneous acquisition of multiple fluorescent wavelengths can be achieved by utilizing concurrent imaging with multiple detectors. However, such class of microscopic systems functions differently from traditional fluorescence microscopes.